Karakteristik Mutu Mie Berbahan Ikan Kembung, Kacang Hijau, dan Daun Kelor untuk Ibu Hamil Kurang Energi Kronis - Nelly Zahra Sarifa; Resty Mauliya Rizky; Fitriana Mustikaningrum Mustikaningrum; Muwakhidah Muwakhidah (Jurnal Teknologi dan Mutu Pangan, 2026)
Pregnant women with chronic energy deficiency (CED) require adequate nutritional intake to support fetal health and growth. Therefore, innovation is needed in the development of supplementary food (PMT) as an alternative to biscuits to increase product variety. This study aims to develop noodles made from local ingredients as PMT for pregnant women with CED as a functional food by identifying the resulting quality characteristics. The research method employed a Completely Randomized Design (CRD) with two formulations composed of mackerel, moringa leaf flour, and mung bean flour: F1 (50:1:50) and F2 (60:1:40), each replicated twice. The parameters tested included moisture content, rehydration capacity, color, and organoleptic properties, which were subsequently analyzed statistically using the independent t-test. The results showed that F1 received the highest overall acceptability score of 5.40±0.985. Additionally, the color test (L*) revealed a significant difference, with F1 exhibiting a higher brightness level than F2. Thus, this study concludes that the PMT noodle formulation based on mackerel, mung beans, and moringa leaves for pregnant women with KEK has sensory characteristics that are acceptable to the panelists. The results of this study have the potential to serve as a high-nutrient PMT alternative based on local foods for pregnant women with KEK.